“Liturgy and Ecumenism, Contexts and Challenges”: A Glance from the African Context - Uzukwu, Elochukwu (Studia liturgica, 2024)
Ecumenical activities in East and West Africa, though modest, represent significant strides for Christianity in the continent of Africa. The narrative in this article, deliberately tilted toward African agency, is an attempt to capture aspects of the story. It begins with the ecumenical liturgical performance of Catholic Kongo-Angola slaves soliciting Holy Communion from Anglican divines, in South Carolina, early in the eighteenth century. Its impact in the overall understanding of ecumenism from the African context is underlined. Next, the article shifts to eastern and western Africa, where a divisive colonial Christian agenda was propagated, and, at the same time, contained, thanks to the initiative of African leadership, guided by the Holy Spirit. Further samples of the Holy Spirit guiding the community to Christian unity are drawn from the witness of the Ugandan martyrs. The article also refers to the liturgical melding of Christian denominations in the Charismatic and Pentecostal patterns of worship as an important statement on liturgical ecumenism.